Нові різновиди модуляції сигналу в цифрових радіорелейних системах передавання - Горбатий, І. В. (ХНУРЭ, 2013)
The family of modulations on the basis of amplitude modulation of many components (AMMC) in the digital radio-relay line-of-sight transmission systems is suggested to use. As a result of researches it sets, that in case of use offer AMMC the distance between the signal points on the signal constellation increases, what is why the bit error rate decrease in radio-relay line-of-sight transmission systems by comparison to the use of quadrature amplitude modulation (QAM) at identical maximal power and informing of modulated signal. It is shown, that offer method of adaptive data transmission in the systems of the remote sensing of Earth, the satellite telecom-munication systems, the radio-relay line-of-sight transmission systems with the use of AMMC allows to increase a quantity of trans-mitted data through radio-relay line-of-sight transmission system on 5,3% because АMMC characterized by higher protect of hin-drance.
Keywords: радіорелейна система передавання прямої видимості; імовірність бітової помилки; амплітудна модуляція багатьох складових; квадратурна амплітудна модуляція